Mobile deep learning projects : 8 project guides to help you work through end-to-end neural network projects on cross-platform apps /: 8 project guides to help you work through end-to-end neural network projects on cross-platform apps. (2020) - Singh, Anubhav; Bhadani, Rimjhim
No abstract available